2017
DOI: 10.1245/s10434-017-6077-y
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Adiposity and Sarcopenic Visceral Obesity are Associated with Poor Prognosis After Resection of Pancreatic Cancer

Abstract: Visceral adiposity and sarcopenic visceral obesity, as well as low muscle mass and quality, were closely associated with mortality and recurrence after resection of pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
129
4
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(145 citation statements)
references
References 38 publications
7
129
4
5
Order By: Relevance
“…Recently, the concept of sarcopenic obesity has been proposed. It has been suggested that sarcopenic obesity is a poor prognostic factor in several malignant diseases [25,26]. In the present study, BMI was higher in the H group than in the N group; thus, the proportion of body fat might also be higher in the H group, suggesting that a high IMAC may be an index of sarcopenic obesity.…”
Section: Discussionsupporting
confidence: 45%
“…Recently, the concept of sarcopenic obesity has been proposed. It has been suggested that sarcopenic obesity is a poor prognostic factor in several malignant diseases [25,26]. In the present study, BMI was higher in the H group than in the N group; thus, the proportion of body fat might also be higher in the H group, suggesting that a high IMAC may be an index of sarcopenic obesity.…”
Section: Discussionsupporting
confidence: 45%
“… 1, Antoun et al (2013); 2, Martin et al (2013); 3, Akahori et al (2015); 4, Aust et al (2015); 5, Fujiwara et al (2015); 6, Malietzis et al , (2015); 7, Malietzis et al , (2016); 8, Malietzis, Johns, et al (2016); 9, Malietzis, Lee, et al (2016); 10, Boer et al (2016); 11, Cushen et al (2016); 12, Hayashi et al (2016); 13, Kumar et al (2016); 14, Pędziwiatr et al (2016); 15, Rollins et al (2016); 16, Sjøblom et al (2016); 17, Tamandl, Pedley, Hoffmann, Fox, and Murabito (2016); 18, Atlan et al (2017); 19, Bye et al (2017); 20, Chu et al (2017); 21, Daly et al (2017); 22, Daly, Ní Bhuachalla, et al (2018); 23, Kubo, Naito, Mori, Osawa, and Aruga (2017); 24, Loumaye et al (2017); 25, Okumura et al (2017a); 26, Okumura et al (2017b); 27, Rier et al (2017); 28, Rier et al (2018); 29, Shachar, Deal, Weinberg, Williams, et al (2017); 30, Shachar, Deal, Weinberg, Nyrop, et al (2017); 31, Van Rijssen et al (2017); 32, van Roekel et al (2017); 33, Williams et al (2017); 34, Williams et al (2018); 35, Choi et al (2018); 36, Deng et al (2018); 37, Ní Bhuachalla et al (2018); 38, Rodrigues and Chaves (2018); 39, Silva de Paula et al (2018); 40, Souza et al (2018); 41, Versteeg et al (2018); 42, Charette et al (2019); 43, Kiss et al (2019); 44, Zhang et al (2018); 45, Dohzono, Sasaoka, Takamatsu, Hoshino, and Nakamura (2019); 46, van Baar et al (2018); 47, Atasevenet et al (2018); 48, Martin et al (2018); 49, Stretch et al (2018); 50, van Dijk et al (2018); 51, van Vugt, Gaspersz, et al (…”
Section: Resultsmentioning
confidence: 99%
“…1, Mayer et al (1989); 2, Goodpaster, Kelley, et al (2000); 3, Hicks et al (2005a); 4, Hicks et al (2005b); 5, Komiya et al (2006); 6, Laroche and Cintas (2010); 7, Anderson et al (2013); 8, Anderson et al (2014); 9, Antoun et al (2013); 10, Miljkovic et al (2013); 11, Therkelsen et al (2013); 12, Therkelsen et al (2016); 13, Kim et al (2014); 14, Akahori et al (2015); 15, Aust et al (2015); 16, Malietzis et al (2015); 17, Malietzis, Currie, et al (2016); 18, Malietzis, Johns, et al (2016); 19, Malietzis, Lee, et al (2016); 20, Cushen et al (2016); 21, Hayashi et al (2016); 22, Kumar et al (2016); 23, Looijaard et al (2016); 24, Montano‐Loza et al (2016); 25, Rollins et al (2016); 26, Wang et al (2016); 27, Atlan et al (2017); 28, Azuma et al (2017); 29, Bye et al (2017); 30, Erlandson et al (2017); 31, Locke et al (2017); 32, Loumaye et al (2017); 33, Okumura et al (2017b); 34, Rier et al (2017); 35, Rier et al (2018); 36, Shachar, Deal, Weinberg, Williams, et al (2017); 37, Shachar, Deal, Weinberg, Nyrop, et al (2017); 38, van Roekel et al (2017); 39, Williams et al (2017); 40, Williams et al (2018); 41, Choi et al (2018); 42, Rodrigues and Chaves, (2018); 43, Silva de Paula et al (2018); 44, Souza et al (2018); 45, Versteeg et al (2018); 46, Charette et al (2019); 47, Kiss et al (2019); 48, Zhang et al (2018); 49, Coats et al (2018); 50, Vella et al (2018); 51, Dohzono et al (2019); 52, van Baar et al (2018); 53, ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The alteration in body composition also makes an impaired response to chemotherapy and radiation therapy in a variety of cancers, making treatments more difficult in these patients. In a retrospective study of pancreatic cancer patients, sarcopenic obesity is associated with lower overall survival and recurrence-free survival [7,17,[73][74][75][76][77][78] Multiple studies of different cancer patients conclude sarcopenic obesity as an independent risk factor on clinical outcomes and overall survival after surgical resection [28,79]. Sarcopenic obesity is also seen as an independent risk factor of mortality in lung, prostate, and GI cancer patients with the locally advanced or metastatic disease [11,[80][81][82][83].…”
Section: Impacts Of Sarcopenic Obesity In Cancer Patientsmentioning
confidence: 99%